Colloid‐Interface‐Assisted Laser Irradiation of Nanocrystals Superlattices to be Scalable Plasmonic Superstructures with Novel Activities. Issue 16 (12th February 2018) - Huang, Liu; Wan, Xiaodong; Rong, Hongpan; Yao, Yuan; Xu, Meng; Liu, Jia; Ji, Muwei; Liu, Jiajia; Jiang, Lan; Zhang, Jiatao
Abstract: High‐efficient charge and energy transfer between nanocrystals (NCs) in a bottom‐up assembly are hard to achieve, resulting in an obstacle in application. Instead of the ligands exchange strategies, the advantage of a continuous laser is taken with optimal wavelength and power to irradiate the film‐scale NCs superlattices at solid–liquid interfaces. Owing to the Au‐based NCs' surface plasmon resonance (SPR) effect, the gentle laser irradiation leads the Au NCs or Au@CdS core/shell NCs to attach each other with controlled pattern at the interfaces between solid NCs phase and liquid ethanol/ethylene glycol. A continuous wave 532 nm laser (6.68–13.37 W cm −2 ), to control Au‐based superlattices, is used to form the monolayer with uniformly reduced interparticle distance followed by welded superstructures. Considering the size effect to Au NCs' melting, when decreasing the Au NCs size to ≈5 nm, stronger welding nanostructures are obtained with diverse unprecedented shapes which cannot be achieved by normal colloidal synthesis. With the help of facile scale‐up and formation at solid–liquid interfaces, and a good connection of crystalline between NCs, the obtained plasmonic superstructured films that could be facilely transferred onto different substrates exhibit broad SPR absorption in the visible and near‐infrared regime, enhanced electric conductivities, and wide applications as surface enhanced Raman scattering (SERS)‐active substrates. Abstract : Colloid interfaces supported film‐scale diverse plasmonic superstructures by gentle continuous laser irradiation of colloidal nanocrystals superlattices have been prepared successfully, which could not be realized by other traditional colloidal synthesis and assembly strategies. Such novel Au‐based plasmonic superstructure films have exhibited broad surface plasmon resonance absorption in both the visible and near infrared regime, enhanced electric conductivities, and wide application as SERS‐active substrates.